Preference for nearshore and estuarine habitats in anadromous Arctic char ( Salvelinus alpinus) from the Canadian high Arctic (Victoria Island, Nunavut) revealed by acoustic telemetry - Moore, Jean-Sébastien; Harris, Les N.; Kessel, Steven T.; Bernatchez, Louis; Tallman, Ross F.; Fisk, Aaron T. (Canadian Journal of Fisheries and Aquatic Sciences, 2016)
We used an array of fixed acoustic receivers (N = 42) to track the summer marine movements of 121 anadromous Arctic char (Salvelinus alpinus) equipped with acoustic transmitters at three locations in the Cambridge Bay region, where commercial and subsistence fisheries target the species. The timing of transitions between salt and fresh water was influenced by the putative river of origin of tagged individuals, but not by their size or sex. Females, however, were more likely to remain proximate to rivers where they were tagged throughout the summer. A majority of fish migrated west from their rivers of origin, primarily moving between estuarine environments. Individuals occupied estuaries for several days between bouts of marine movement, and these periods of residency coincided with spring tides in some estuaries. We also recorded increased numbers of detections on receivers located less than 1.5 km from the coast, indicating a preference for nearshore habitats. Finally, we report evidence of extensive stock mixing throughout the summer, including at known fishing locations and periods, a finding with implications for fisheries management.